The interest of the millenial generation to invest in the sharia market through fintech technology - Nur Kabib; Arum Nur Aisyah; Fitri Khofifah (Islamic Accounting Journal, 2021)
The purpose of this study was to examine the influence of investment knowledge, personal and environmental interests on online investment interest. This type of research uses quantitative methods with primary data collection through questionnaires. The analytical method used is multiple linear regression as measured by SPSS 20. The results of this study indicate that investment knowledge, personal interests, and the environment have a significant positive effect on online investment interest. It can also be concluded that all independent variables have a significant effect on the dependent variable on online investment interest.Keywords: Investment knowledge, personal interest, environment, and financial technology